Biodiesel from non-edible Karanja seed oil (Bangladesh Journal of Scientific and Industrial Research, 2017)
The fossil fuel resources are dwindling day by day. Fuel has been a challenge for todays scientific works for increasing demand. The methyl esters of vegetable oils, known as biodiesel are becoming increasingly well known because of their low environmental impact. Methyl esters of Pongamiapinnata are derived through esterification and transesterification. Several processes of biodiesel fuel production has been developed, among which transesterification using alkali as a catalyst gives high level of conversion of triglycerides to their corresponding methyl ester in a short duration. Amount of solvent, catalyst, temperature and reaction time were optimizedfor estimates the conversion efficiency. The physical properties of Karanja seed oil (KSO) and biodiesel were studied and compared with standard. FTIR and TGA spectrums of KSO and KSO Biodiesel were studied for the confirmation of conversion.Bangladesh J. Sci. Ind. Res. 52(1), 15-20, 2017